2004
DOI: 10.1038/labinvest.3700132
|View full text |Cite
|
Sign up to set email alerts
|

Possible involvement of MIP-1α in the recruitment of osteoclast progenitors to the distal tibia in rats with adjuvant-induced arthritis

Abstract: In the rat model of rheumatoid arthritis, a marked formation of osteoclasts is found in the distal tibia and the metatarsal bone. It was therefore postulated that osteoclast progenitors would be increased in the bone marrow cavities of rats with adjuvant-induced arthritis (AA rats). Bone marrow cells obtained from tibia of AA rats were cultured to form cells in the osteoclast lineage to access the number of osteoclast progenitors. Unexpectedly, only a suppressed level of osteoclast progenitors was detected in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
36
0
3

Year Published

2005
2005
2019
2019

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 41 publications
(41 citation statements)
references
References 27 publications
2
36
0
3
Order By: Relevance
“…The CFAinduced clinical symptoms were similar to those in our previous studies. [27][28][29] To focus on the effects of PSLs on AAinduced inflammatory bone loss, systemic treatment with PSLs was begun 10 days after CFA injection, when the inflammation was established without bone destruction in the ankle joint. Treatment with PSLs for 18 days significantly reduced the paw volume and resulted in a marked increase in the synovial thickness of ankle joints in AA rats during the chronic stage, without any significant effect during the acute stage (Figure 1a-c; horizontal bars).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The CFAinduced clinical symptoms were similar to those in our previous studies. [27][28][29] To focus on the effects of PSLs on AAinduced inflammatory bone loss, systemic treatment with PSLs was begun 10 days after CFA injection, when the inflammation was established without bone destruction in the ankle joint. Treatment with PSLs for 18 days significantly reduced the paw volume and resulted in a marked increase in the synovial thickness of ankle joints in AA rats during the chronic stage, without any significant effect during the acute stage (Figure 1a-c; horizontal bars).…”
Section: Resultsmentioning
confidence: 99%
“…22 Among anti-inflammatory mediators, including TGF-b1 and PGE 2 , IL-10 is known as the strongest feedback mediator of inflammatory bone loss. 23,24 The paw volume increase of adjuvant arthritic (AA) rat, an animal model of RA, [25][26][27] occurs in two stages: namely an acute inflammation stage from 10 to 21 days after complete Freund's adjuvant (CFA) injection, and the chronic bone/ joint destruction stage thereafter. Therefore, in our previous study, to examine the direct effect of PSLs on osteoclastogenesis, the treatment of PSLs was started prior to the formation of osteoclasts in AA rats (14 days after CFA injection).…”
mentioning
confidence: 99%
“…26 Five-week-old female Lewis rats were anesthetized with diethyl ether and were intradermally injected at the base of the tail with complete Freund adjuvant (CFA) containing 25 mg/kg heat-killed M. butyricum (Difco Laboratories) suspended in mineral oil. In control experiments, rats were injected with mineral oil alone.…”
Section: Induction Of Adjuvant Arthritis In Lewis Rats and Administramentioning
confidence: 99%
“…25 MIP-1a is highly expressed in the areas of severe bone destruction of the distal tibia of AA-rats. 26 MIP-1a is also involved in pathological osteoclastogenesis associated with multiple myeloma. 27,28 Another chemokine, stromal-derived factor 1 a (SDF-1a/CXCL12), a CXC chemokine having potential ability to support hematopoietic stem cells and progenitors, 29 has the ability to promote migration of inflammatory cells in vitro.…”
mentioning
confidence: 99%
“…14,15 We have previously shown lines of evidence suggesting the involvement of the chemokine MIP-1a in the process of bone destruction accompanying adjuvant-induced arthritis (AA) in rats. 16 Recently, it has been reported that anti-inflammatory drugs such as leflunomide, tacrolimus, and cyclosporine A suppress bone destruction through direct inhibition of RANKL-mediated osteclastogenesis. 17,18 These findings are suggesting the availability of anti-inflammatory drugs or cytokines as the suppressor of bone destruction.…”
mentioning
confidence: 99%